2017
DOI: 10.1007/s00167-017-4521-y
|View full text |Cite
|
Sign up to set email alerts
|

No differences in subjective knee function between surgical techniques of anterior cruciate ligament reconstruction at 2-year follow-up: a cohort study from the Swedish National Knee Ligament Register

Abstract: PurposeThe purpose of this study was to investigate how different techniques of single-bundle anterior cruciate ligament (ACL) reconstruction affect subjective knee function via the Knee injury and Osteoarthritis Outcome Score (KOOS) evaluation 2 years after surgery. It was hypothesized that the surgical techniques of single-bundle ACL reconstruction would result in equivalent results with respect to subjective knee function 2 years after surgery.MethodsThis cohort study was based on data from the Swedish Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…Some of the limitations of this study include a lack of pre-operative KOOS data, which means we were unable to accurately determine the change in KOOS scores between groups; however, the post-operative KOOS scores are excellent in both groups and consistent with other reported outcomes [9, 16]. Clinical follow-up was performed by unblinded staff, and graft type (autograft or allograft) had an uneven distribution between groups.…”
Section: Discussionmentioning
confidence: 89%
“…Some of the limitations of this study include a lack of pre-operative KOOS data, which means we were unable to accurately determine the change in KOOS scores between groups; however, the post-operative KOOS scores are excellent in both groups and consistent with other reported outcomes [9, 16]. Clinical follow-up was performed by unblinded staff, and graft type (autograft or allograft) had an uneven distribution between groups.…”
Section: Discussionmentioning
confidence: 89%
“…But, Ardern et al 49 reported less than 50% of the patients returned to the preinjury level, or to competitive sport participation during the 2 to 7 years after ACLR. Hamrin et al 50 found that single-bundle ACLR did not significantly improve subjective knee function through the KOOS evaluation after 2 consecutive annual clinic visits. This study also found that preoperative (after injury) subjective scores were lower than postoperative subjective scores and postoperative subjective scores were lower than preinjury subjective scores as measured with Tegner activity level.…”
Section: Discussionmentioning
confidence: 99%
“…The target is 100% coverage of the number of registered operation reports. A yearly check is made with the Swedish Board of Health and Welfare regarding the ID number [5]. The register is in line with the Swedish legislation on data security.…”
Section: Swedish National Knee Ligament Registry (Sklr)mentioning
confidence: 99%